Cognitive Performance and Psychological Distress in Breast Cancer Patients at Disease Onset - Kaiser, Jochen; Dietrich, Jörg; Amiri, Miena; Rüschel, Isa; Akbaba, Hazal; Hantke, Nonda; Fliessbach, Klaus; Senf, Bianca; Solbach, Christine; Bledowski, Christoph (Frontiers in Psychology, 2019)
Objective: Many cancer patients complain about cognitive dysfunction. While cognitive deficits have been attributed to the side effects of chemotherapy, there is evidence for impairment at disease onset, prior to cancer-directed therapy. Further debated issues concern the relationship between self-reported complaints and objective test performance and the role of psychological distress. Method: We assessed performance on neuropsychological tests of attention and memory and obtained estimates of subjective distress and quality of life in 27 breast cancer patients and 20 healthy controls. Testing in patients took place shortly after the initial diagnosis, but prior to subsequent therapy. Results: While patients showed elevated distress, cognitive performance differed on a few subtests only. Patients showed slower processing speed and poorer verbal memory than controls. Objective and self-reported cognitive function were unrelated, and psychological distress correlated more strongly with subjective complaints than with neuropsychological test performance. Conclusions: This study provides further evidence of limited cognitive deficits in cancer patients prior to the onset of adjuvant therapy. Self-reported cognitive deficits seem more closely related to psychological distress than to objective test performance.